2020
DOI: 10.31538/ndh.v5i3.967
|View full text |Cite
|
Sign up to set email alerts
|

How the Research Skills Development Framework May Be Useful for Indonesian Higher Education Learning Practice

Abstract: This qualitative research aimed to review the usefulness of Research Skills Development framework (RSD) among higher education students in Indonesia. The RSD concept has contributed to research-based learning models among students in Australia, both among elementary and tertiary school students. Due to this research framework's success in Australia, we plan to review and see the usefulness of the RSD framework to university students in Indonesia. To facilitate this introduction, we have tried to review several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The results showed that (1, both the achievement of cognitive, affective, and psychomotor learning outcomes (Sota & Peltzer, 2017). Research activities facilitate students with research skills that are essential to their education (Hutagaluh et al, 2020) and construct their own knowledge (Wannapiroon, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that (1, both the achievement of cognitive, affective, and psychomotor learning outcomes (Sota & Peltzer, 2017). Research activities facilitate students with research skills that are essential to their education (Hutagaluh et al, 2020) and construct their own knowledge (Wannapiroon, 2014).…”
Section: Introductionmentioning
confidence: 99%